Penerapan Metode Snowball Throwing untuk Meningkatkan Motivasi Belajar Bahasa Arab Siswa Kelas VII di Madrasah Tsanawiyah Negeri 1 Luwu Timur - Kartini; Nurmiati; Fatina Adzkia Al-Azka (JURNAL ILMIAH NUSANTARA, 2025)
This study aims to enhance students' learning motivation in Arabic language classes using the snowball throwing method. This method is designed to create an engaging and interactive learning environment while fostering students' confidence, responsibility, mutual respect, and enthusiasm for learning. The research employed a classroom action research approach conducted in two cycles, each consisting of planning, implementation, observation, and reflection phases. Each cycle was completed in one session with an allocated time of 2 x 40 minutes. The results indicate a significant improvement in the implementation of teaching modules by the teacher, students' learning activities, and their learning motivation. In Cycle I, the implementation of the teaching module by the teacher reached 63.4% (categorized as good) and increased to 84.6% (categorized as very good) in Cycle II. Similarly, students' learning activities improved from 67.6% (good) in Cycle I to 91.1% (very good) in Cycle II. Moreover, students' average learning motivation scores rose from 42.1 (65%) in Cycle I to 52.9 (82%) in Cycle II. These findings demonstrate that the snowball throwing method is effective in enhancing students' learning motivation in Arabic language classes.